2017
DOI: 10.2169/internalmedicine.56.7438
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Cryptococcosis with Rapidly Growing Lung Nodules in an End-stage Renal Disease Patient

Abstract: A 73-year-old man with type 2 diabetes mellitus and end-stage renal disease was diagnosed with acute myocardial infarction. He required continuous dialysis after percutaneous coronary intervention. Subsequently, multiple nodules were discovered in both lungs for the first time, and Cryptococcus neoformans was isolated from the patient's sputum, blood, bilateral pleural fluid, and cerebrospinal fluid cultures, resulting in a diagnosis of disseminated cryptococcosis. This case represents an invaluable example of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…To our best knowledge, this was the first report to clarify the clinical manifestations of advanced CKD in patients with non-HIV pulmonary cryptococcosis. CKD is one of the risk factors for pulmonary cryptococcosis; this statement can be supported by several individual cases that had severe clinical manifestations, such as dissemination and mortality, in chronic renal failure, especially when under dialysis [14,20]. Pyrgos V et al reported that compared with all hospitalized patients, those hospitalized for cryptococcus meningitis had significantly more frequent comorbidities of acute (28.5%) and chronic renal failure (14.3%) [24].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To our best knowledge, this was the first report to clarify the clinical manifestations of advanced CKD in patients with non-HIV pulmonary cryptococcosis. CKD is one of the risk factors for pulmonary cryptococcosis; this statement can be supported by several individual cases that had severe clinical manifestations, such as dissemination and mortality, in chronic renal failure, especially when under dialysis [14,20]. Pyrgos V et al reported that compared with all hospitalized patients, those hospitalized for cryptococcus meningitis had significantly more frequent comorbidities of acute (28.5%) and chronic renal failure (14.3%) [24].…”
Section: Discussionmentioning
confidence: 96%
“…There is increasing evidence that CKD is closely linked with host immune systems [18] and the risk for infections [19]. Some reports identified that the severity of CKD was involved with the clinical characteristics of pulmonary cryptococcosis [20,21]; however, the clinical features have not been fully assessed.…”
Section: Introductionmentioning
confidence: 99%
“…CKD is one of the risk factors for pulmonary cryptococcosis; this statement can be supported by several individual cases that had severe clinical manifestations, such as dissemination and mortality, in chronic renal failure, especially when under dialysis (14,20). Pyrgos V et al reported that compared with all hospitalized patients, those hospitalized for cryptococcus meningitis had significantly more frequent comorbidities of acute (28.5%) and chronic renal failure (14.3%) (24).…”
Section: Discussionmentioning
confidence: 96%
“…Currently, it is becoming an important infection in human immunodeficiency virus-negative patients [ 11 ], particularly in those with significant underlying immunosuppression such as organ transplant, long-term glucocorticoid treatment, hematologic malignancies, diabetes mellitus, hepatic cirrhosis, among others [ 12 , 13 ]. In China, pulmonary cryptococcosis ranked as the third most common pulmonary fungal infection, and most Chinese patients with pulmonary cryptococcosis do not have underlying diseases [ 14 ]. Our patient was an immunocompetent patient without an immunity-associated medical history.…”
Section: Discussionmentioning
confidence: 99%